The Success of Digital Transformation through Cloud: Revolutionary Innovation at PT Telekomunikasi Selular Indonesia - Arliadinda Danusaputro; Dodie Tricahyono; Moh Riza Sutjipto (International Journal of Social Science and Business, 2024)
The competitiveness in the digital era is strengthened by many companies through digital transformation, such as PT Telekomunikasi Selular Indonesia, which adopted cloud computing. However, they faced increased service disruptions and usage costs exceeding the initial design in the early stages of implementation. This study aims to analyses the crucial factors determining the success of digital transformation in the implementation of cloud technology at PT Telkomsel. In this research, the phenomenon under study is explored through a case study approach, utilizing Creswell's Data Analysis Technique and triangulation validation tests, including in-depth interviews, observations, and secondary data collection. The informants involved in this research are internal and external experts in their fields and are involved in this cloud project. In addition to involving informants from the IT department, informants from other departments are also involved to provide a comprehensive understanding of this research. The Critical Success Factors (CSF) model for cloud projects by Corriea and Martens (2022) is used as a framework to identify the determining factors for the success of a cloud project. The analysis results show that people, change management, contract, and communication are factors of concern in the success of digital transformation in the implementation of cloud technology at PT Telkomsel. Thus, this research provides valuable insights to improve strategy and approach in cloud implementation and serves as a learning resource for other organizations undergoing digital transformation using cloud technology.